Instructors-as-researchers-and-theorists: Action research in a community college - John M. Peters (Adult Education Research Conference, 1994)
Instructors in a community college engaged in reflective practice undertook action research projects in order to improve their teaching practices. Collaborative inquiry and learning resulted in individual and collective change in assumptions, ideas and practices.